EFFECTIVENESS OF MICROPLASTIC REDUCTION IN ELECTROCOAGULATION OF WASTE MASKS WITH Fe-Al-Fe-Al ELECTRODES - Anggraini, Ardhita Julia (Jurnal Elemen Kimia, 2025)
Surgical mask waste has increased since pandemic and having an impact due to release of microplastics in aquatic environment. This study aims to determine functional group characteristics of surgical masks before and after removing microplastics, floc characteristics in terms of functional groups, effect of 0.01M Na2SO4 volume, electrocoagulation time and solution pH on effectiveness of reducing microplastics.This study used samples in form of surgical mask waste which is taken for microplastics by immersing them in aquabidest for approximately 50 days. The microplastic samples are separated from liquid and analyzed by FTIR. The next step is electrocoagulation process with a current 2,5 A for variations volume of 0,01 M Na2SO4, electrocoagulation time, and pH of solution. The flocs are characterized with FTIR and SEM, liquid samples are analyzed for number of fibers using a 40x magnification microscope.The results of this study indicate that surgical masks before and after removing microplastics contain functional groups which indicate presence of polypropylene (PP) and polyvinylchloride (PVC). The floc character indicates presence of plastic polymers, especially polypropylene (PP) and polyvinylchloride (PVC), and appearance of floc grains is quite smooth and compact. Variations volume of 0,01 M Na2SO4, more volume added then higher reduction effectiveness value, but too much volume added causes solution concentrated. Variations electrocoagulation time, longer electrocoagulation time, higher reduction effectiveness value, but too long electrocoagulation causes passive electrode. Variations pH of solution, solution closer to pH 6 has a higher reduction effectiveness value and solution pH more than 6 resulted floc stabilization. Keywords:medical surgical masks, microplastics, electrocoagulation, effectiveness